The effect of musical mnemonics on learning and recall in preschool-aged children with developmental disabilities - Selph, Audrey, author; LaGasse, Blythe, advisor; Thaut, Michael, advisor; Davalos, Deana, committee member (Colorado State University. Libraries, 2015)
The purpose of this study was to assess whether musical mnemonics rehearsal is more effective than verbal rehearsal on immediate and delayed recall of novel information for preschool-aged children with developmental delays. Forty 3- to 5-year old children in a special education program were selected from a prescreening process as participants. Participants were randomly divided into two groups by a computerized randomizer. Group 1 received all input in spoken format and Group 2 received all input in sung format. All participants listened to a random, non-repetitive seven-digit number. Sung numbers matched the opening phrase of "Old MacDonald." For each trial, the researcher played the pre-recorded number five times. The number of correct consecutive digits was recorded both at the end of each hearing, after a one-minute distraction and following a five minute delay. Since there was evidence of skew in the serial order recall results, serial scores were compared within group and across groups using non-parametric statistical analysis. Results showed no significant difference between the music and non-music groups. Overall serial order recall scores were low, suggesting that the digit span was beyond the developmental capabilities of many of the participants. There was a significant effect of time and age, however. Paired comparisons showed significantly greater recall in Trial 4 versus Trial 1, and in Trial 5 versus delayed recall, suggesting both an increase in recall due to learning and a decrease in recall after the 5-minute delay and distraction activity. Five-year olds also performed significantly better than 3-4 year olds on delayed absolute recall and immediate serial order recall. Future research suggestions are discussed.
Keywords: disability; music therapy; recall; mnemonics; developmental; preschool